(Dis-)Embodied Experiences: A Comprehensive Study of Mobility Aids in the Miracles of Saint Louis - Dubourg, Ninon (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2026)
This article examines the material history of medieval disability by studying two manuscripts of the Miracles of Saint Louis from the fourteenth and fifteenth centuries. It argues that mobility aids not only rendered disability visible to medieval eyes and the historical record — much like the modern perception of the wheelchair— but also “augmented” the disabled body, enabling new forms of movement and autonomy. Adopting a cross-disciplinary and comparative approach, this study examines the diverse designs of mobility aids and their adaptability to the specific needs of individuals, depending on their environment. Far from being passive objects, these aids actively extended the body’s capabilities, transforming the impairment experience into one of greater mobility and agency. They also invite a reconsideration of embodiment itself, as the use of these aids blurred the boundaries between object and subject, physicality and identity. These material, inanimate objects become animated with the body, and inseparable from it, to the point of being bound to it, whether physically or socially. By tracing how these tools facilitated movement and autonomy, this article sheds light on the evolving phenomenological experience of non-standard embodiment, challenging modern assumptions and revealing the cultural significance of disability in the medieval world.